2012
DOI: 10.1097/iae.0b013e318256205a
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Depth Imaging Optical Coherence Tomography of the Choroid in Vogt–koyanagi–harada Disease

Abstract: Enhanced depth imaging-optical coherence tomography revealed decreasing choroidal thickness with high-dose corticosteroid treatment in our patients. Choroidal thickness as measured by EDI-OCT may serve as a marker for degree of choroidal inflammation in acute VKH disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
98
0
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(113 citation statements)
references
References 15 publications
(18 reference statements)
3
98
0
8
Order By: Relevance
“…In patients with acute VKH disease, EDI-OCT images clearly showed bilateral diffusely thickened choroids that decreased over time with corticosteroid treatment [4][5][6]. In the current case, we clearly visualized the full-thickness choroid except in the untreated phase and the decreasing choroidal thickness during tapering of oral prednisolone.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…In patients with acute VKH disease, EDI-OCT images clearly showed bilateral diffusely thickened choroids that decreased over time with corticosteroid treatment [4][5][6]. In the current case, we clearly visualized the full-thickness choroid except in the untreated phase and the decreasing choroidal thickness during tapering of oral prednisolone.…”
Section: Discussionsupporting
confidence: 49%
“…Nakayama et al [5] defined rebound choroidal thickening as an increase exceeding 100 μm over the previous lowest measurement obtained during corticosteroid tapering; they reported that five eyes with rebound choroidal thickening had no recurrent inflammation by slit-lamp biomicroscopy or funduscopy during follow-up. However, Nakai et al [6] reported that a SRD developed again in four eyes with anterior inflammation and the choroidal thickness again increased markedly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EDI-OCT studies into other uveitic conditions such as Vogt-Koyanagi-Harada disease 23 and Behçet's disease 45 have observed a thicker choroid in active compared with quiescent disease. A possible explanation for this observation is that in the presence of inflammation, the release of mediators such as prostaglandins causes blood vessels to dilate leading to increases in OCT-derived measurements of choroidal thickness.…”
Section: The Choroid In Granulomatous Uveitismentioning
confidence: 99%
“…For example, OCT has been used (1) to describe characteristic features of specific uveitis entities, including thinning of Haller's large vessel layer of the choroid in idiopathic panuveitis and extra-macular choroidal changes in birdshot chorioretinopathy; 18,19 (2) to identify distinct stages of a disease process as illustrated by punctate inner choroidopathy; 20,21 (3) objective measurement of vitreous inflammation; 22 and (4) to monitor response to therapy, exemplified by a reduction of subfoveal choroidal thickening with corticosteroid therapy in Vogt-KoyanagiHarada disease. 23 Additionally, the potential of OCT angiography in uveitic diseases has yet to be realised.…”
Section: Introductionmentioning
confidence: 99%